Effect of slow breathing exercise on heart rate variability: A non linear analysis in female major depressive disorder patients - Zaman, Nusrut; Sultana, Shamima; Morshed , Nahid Mahjabin; Chowdhury, Esha; Lima, MarefaTuz Zohora (Journal of Bangladesh Society of Physiologist, 2024)
Background: Major depressive disorder (MDD) is a mental health problem, associated with cardiac autonomic dysfunction. Cardiac autonomic function (CANF) can be assessed by non linear analysis of heart rate variability (HRV), a simple non-invasive software based analytical method. Yoga based slow breathing exercise (SBE) has role to improve autonomic dysfunction in some disease condition. Objective: To observe the effect of SBE on non linear measures of HRV in newly diagnosed female MDD patients. Methods: The quasi-experimental study was conducted in 2023 on sixty (60) newly diagnosed female MDD patients of 20-40 years aged, collected from the Department of Psychiatry, Bangabandhu Sheikh Mujib Medical University (BSMMU). Among them 30 were assigned with SBE and remaining 30 patients without SBE were followed up after 90 days. Both patient groups received conventional treatment during this period. Thirty apparently healthy female subjects with similar age & BMI were included as control for comparison and they did not perform breathing exercise. Data were taken at baseline and after 90 days in all the subjects. CANF was assessed by analysing non linear (poincare plot) of HRV by using ECG based data acquisition device, Power lab 8/35. Data were expressed as mean±SD. For statistical analysis, ANOVA followed by post hoc Bonferroni test and paired sample “t” test were used. Results: At baseline pulse rate and BP were significantly lower in both group of MDD patients compared to control. The pre-intervention values of standard deviation of short term RR interval variability (SD1), standard deviation of long term RR interval variability (SD2) and ratio of short term and long term RR interval variability (SD1/SD2) were found significantly (p< 0.001) lower in MDD patients compared to healthy control. Following 90 days of SBE, significant (p< 0.001, p< 0.05) rise of these poincare plot parameters was noted in MDD patients whereas no significant changes of these parameters were observed in patients without SBE after 90 days of follow-up. Moreover, the pulse BP almost reached control level though the non linear parameters were still below control level after 3 months of SBE.. Conclusion: Autonomic dysfunction occured in MDD patients SBE can improve cardiac autonomic dysfunction and sympathovagal balance in female MDD patients. J Bangladesh Soc Physiol 2023;18(2): 45-52